TRANSFORMATION OF VALUES OF STUDENT YOUNG PEOPLE: MYTH AND REALITY - I. Maloletneva; Z. Zhiratkova; T. Eliarova (Вестник университета)
Results of a research of student’s valuable orientations of two Moscow higher education institutions - Bauman Moscow State Technical University (National Research University) and Russian International Academy for Tourism (Moscow branch) are considered). The respondents representing higher education institutions, various on professional directions, have chosen as priority identical social and personal resources for achievement of success that demonstrates steady structure of representations at modern Russian student’s youth. The comparative analysis of results of a similar research is provided in the Ogarev Mordovia State University in 2004. Solutions of problems successful social, including professional are offered, to socialization of student’s youth.